2015
DOI: 10.1111/fog.12098
|View full text |Cite
|
Sign up to set email alerts
|

Larval population structure of Engraulis encrasicolus in the Strait of Sicily as revealed by morphometric and genetic analysis

Abstract: In order to investigate the larval population structure, specimens of Engraulis encrasicolus larvae from five different locations in the Strait of Sicily were analyzed by means of otolith readings, morphometric and genetic techniques. The distribution of age in day, identified by means of the otolith readings and associated with the oceanographic parameters, was useful to identify possible spawning areas and transport dynamics. The presence of more than one spawning area suggested the possibility that two or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…In this framework, our findings suggest that mortality of anchovy larvae caused by starvation is expected to be low along their trajectories and hence indicates significant connectivity among GSAs. These results are consistent with Cuttitta et al 41 , which characterized the genetic structure of the European anchovy populations in the Strait of Sicily. These authors found the existence of two different phylogroups probably differentiated during the Pliocene–Pleistocene period and currently not geographically separated.…”
Section: Discussionsupporting
confidence: 93%
“…In this framework, our findings suggest that mortality of anchovy larvae caused by starvation is expected to be low along their trajectories and hence indicates significant connectivity among GSAs. These results are consistent with Cuttitta et al 41 , which characterized the genetic structure of the European anchovy populations in the Strait of Sicily. These authors found the existence of two different phylogroups probably differentiated during the Pliocene–Pleistocene period and currently not geographically separated.…”
Section: Discussionsupporting
confidence: 93%
“…It was characterized by a very complex sea circulation that can have strongly influenced the spawning strategy and the recruitment success of many fish species (Cuttitta et al, 2003Fortibuoni et al, 2010;Garofalo et al, 2010). In particular, many studies Cuttitta et al, 2015;Falcini et al, 2015;García Lafuente et al, 2002) have focused on the influence of oceanographic factors on the ecology and reproductive biology of the European anchovy (Engraulis encrasicolus), which is the target species of fisheries along the southern coast of Sicily, representing one of major fish resource in terms of economic importance (Patti et al, 2005(Patti et al, , 2012. In this study, the influence of the circulation pattern in the Strait of Sicily on the distribution of fish larvae was very clear and it can be considered the main factor governing the larval fish retention and shaping the observed assemblages.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…All these environmental features are known to modify the temperature regime of the surface waters in the Sicilian anchovy habitat [ 21 , 22 ]. Although the Sicilian Channel can be considered a key zone in the Mediterranean basin for the European anchovy population structure, few genetic studies [ 23 ] have been carried out in this area that was identified by Garcia Lafuente et al [ 24 ] as one of the main spawning area of E . encrasicolus .…”
Section: Introductionmentioning
confidence: 99%